“The more children you have, the more praise you get from the community”: exploring the role of sociocultural context and perceptions of care on maternal and newborn health among Somali refugees in UNHCR supported camps in Kenya - Stephanie Gee; Josep Vargas; Angel M. Foster (Conflict and Health, 2019)
Abstract Background Maternal and neonatal survival are key components of population health and may be particularly vulnerable in humanitarian contexts of civil unrest and displacement. Understanding what factors contribute to poor health outcomes throughout the reproductive life cycle and across the continuum of care is crucial for improving health programming in acute and protracted refugee settings. Methods We undertook a mixed-methods baseline assessment of factors related to maternal and neonatal health among refugees living in the Dadaab refugee complex in eastern Kenya. The qualitative component included 23 focus group discussions with 207 community members and 22 key informant interviews with relevant UN and non-governmental organization staff, community leaders, health managers, and front-line health care providers. We analysed qualitative data for content and themes using inductive and deductive techniques. Results Taking a life course perspective, we found that the strong desire for large families and the primary social role of the woman as child bearer impacted maternal and neonatal health in the camps through preferences for early marriage, low demand for contraception, and avoidance of caesarean sections. Participants described how a strong fear of death, disability, and reduced fecundity from caesarean sections results in avoidance of the surgery, late presentation to the health facility in labour, and difficulty gaining timely informed consent. Mistrust of health service providers also played a role in this dynamic. In terms of newborn care practices, while breastfeeding is culturally supported and women increasingly accept feeding colostrum to the newborn, mixed feeding practices and application of foreign substances to the umbilicus continue to present risks to newborn health in this community. Conclusions The findings from our study showcase the role that specific sociocultural beliefs and practices and perceptions of health care services have on maternal and neonatal health. An in-depth understanding of how these factors impact the utilization of biomedical health services provides valuable information for targeted improvements in health service provision that are tailored to the local context.